2011
DOI: 10.1111/j.1475-6773.2011.01326.x
|View full text |Cite
|
Sign up to set email alerts
|

The Health Care Cost Implications of Overweight and Obesity during Childhood

Abstract: Objective. To investigate whether childhood overweight at age 4-5 increases publicly funded health care costs during childhood, and to explore the role of timing and duration of overweight on health costs. Data Sources. The Longitudinal Study of Australian Children (2004Children ( -2008 and linked records from Medicare, Australia's public health insurance provider (2004)(2005)(2006)(2007)(2008)(2009). Study Design. The influence of overweight status on non-hospital Medicare costs incurred by children over a 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…Briefly, the study included 667 first time mothers and their infants, recruited from antenatal clinics in a socially and economically disadvantaged area of Sydney. The intervention consisted of eight home visits by specially trained community nurses, including one visit at 30-36 weeks gestational age, and seven visits at 1,3,5,9,12,15, and 24 months after birth. These visits included one-on-one consultations of 1-h duration at which age-appropriate education and advice on feeding, nutrition and physical activity were provided.…”
Section: Randomized Controlled Trialmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, the study included 667 first time mothers and their infants, recruited from antenatal clinics in a socially and economically disadvantaged area of Sydney. The intervention consisted of eight home visits by specially trained community nurses, including one visit at 30-36 weeks gestational age, and seven visits at 1,3,5,9,12,15, and 24 months after birth. These visits included one-on-one consultations of 1-h duration at which age-appropriate education and advice on feeding, nutrition and physical activity were provided.…”
Section: Randomized Controlled Trialmentioning
confidence: 99%
“…Such data are of concern not only due to the potential for persistence of overweight and obesity from childhood into adulthood (3,4) and the escalating cost and health burden that ensues, but also because of the more immediate health impacts on young children and increased costs to the government. An analysis of linked data has shown that overweight and obesity among children aged 4-5 years are responsible for an additional $AUD $9.8million in spending by the Australian public health system between ages 5 and 10 years (5). Similar effects have been found in the United Kingdom, where 6% of National Health Service costs amongst children have been attributed to elevated BMI (6), and in the United States, where obesity in childhood is associated with greater prescription drug use, outpatient visits and emergency visits (7).…”
Section: Introductionmentioning
confidence: 99%
“…Childhood obesity is also estimated to impose a heavy economic burden on society, and has been estimated to be responsible for 2.0-3.5 per cent of medical expenditure (Thompson and Wolf, 2001). Many studies confirm that the costs of medical services among obese children are significantly higher than those of children within a healthy weight range (Wenig et al, 2011;Kuhle et al, 2011;Au, 2012). In Australia, the estimated direct and indirect costs of obesity and obesity-related illnesses was $37.7 billion in 2008/09, whereas the costs related to productivity loss due to absenteeism and premature death was estimated to be $6.4 billion per year (Medicare Australia, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a very large and costly burden [1,2]. There has been an explosive increase worldwide in the incidence of obesity across age groups [3].…”
Section: Introductionmentioning
confidence: 99%